Parkinsonism in the psychiatric setting: an update on clinical differentiation and management. Issue 1 (27th January 2020) - Powell, Alice; Gallur, Lara; Koopowitz, Leslie; Hayes, Michael William
Abstract : Parkinsonism is seen frequently in patients with psychiatric conditions. Drug-induced parkinsonism (DIP) is the second most common cause of parkinsonism in the general population after Parkinson's disease (PD) but a range of rarer aetiologies, some of them reversible, should also be considered in patients of all ages. DIP is more common in older patients, as are neurodegenerative diseases that may produce parkinsonism and it is relatively more likely that drug exposure could be unmasking an underlying process in this population. There is an extensive literature on differentiating DIP from PD but clinical features can be indistinguishable and many proposed investigations are not readily available. Aside from cessation of the responsible medication, there is no clear consensus on treatment strategies or duration of treatment. Practically, a delicate balance must be achieved between ameliorating parkinsonism and avoiding recurrent psychosis. Long-term prognosis in the setting of DIP remains unclear. We review the features that may differentiate DIP from other causes of parkinsonism in patients with psychiatric illness, provide an update on relevant investigations and discuss management strategies. The use of atypical antipsychotics for a broad range of indications highlights the ongoing relevance of DIP.